2022
DOI: 10.1200/jco.2022.40.16_suppl.9000
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of anti–PD-(L)1 therapy with or without chemotherapy (chemo) for first-line (1L) treatment of advanced non–small cell lung cancer (NSCLC) with PD-L1 score ≥ 50%: FDA pooled analysis.

Abstract: 9000 Background: FDA-approved 1L treatment options for patients with PD-L1-high advanced NSCLC (PD-L1 score ≥50%) include IO ± chemo (± anti-angiogenics) but it is unclear if chemo substantially improves efficacy outcomes when added to IO in this patient population. Methods: Data was pooled from 12 randomized controlled trials that investigated anti-PD-(L)1 regimens ± chemo for the 1L treatment of patients with advanced NSCLC. PD-L1 score was defined as the proportion of tumor cells stained by the assay and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 0 publications
0
25
0
2
Order By: Relevance
“…26 A recent pooled analysis suggested that most patient subgroups with PD-L1 $ 50% receiving FDA-approved immunotherapy and chemotherapy combinations had comparable survival outcomes versus immunotherapy only although of note, dual nivolumab plus ipilimumab was included in the immunotherapy-only group together with anti-PD-(L)1 monotherapies, confounding direct extrapolations. 27 Overall, the optimal regimen for the PD-L1 $ 50% subgroup is unclear, highlighting the importance of considering both risks and benefits of different treatments in individual patients. With nivolumab plus ipilimumab, 18% of patients in CheckMate 227 overall discontinued treatment because of TRAEs, which is not substantially higher than the 14% pembrolizumab discontinuation rate for patients with PD-L1 $ 50% in KEYNOTE-024.…”
Section: Eq-5d Vasmentioning
confidence: 99%
“…26 A recent pooled analysis suggested that most patient subgroups with PD-L1 $ 50% receiving FDA-approved immunotherapy and chemotherapy combinations had comparable survival outcomes versus immunotherapy only although of note, dual nivolumab plus ipilimumab was included in the immunotherapy-only group together with anti-PD-(L)1 monotherapies, confounding direct extrapolations. 27 Overall, the optimal regimen for the PD-L1 $ 50% subgroup is unclear, highlighting the importance of considering both risks and benefits of different treatments in individual patients. With nivolumab plus ipilimumab, 18% of patients in CheckMate 227 overall discontinued treatment because of TRAEs, which is not substantially higher than the 14% pembrolizumab discontinuation rate for patients with PD-L1 $ 50% in KEYNOTE-024.…”
Section: Eq-5d Vasmentioning
confidence: 99%
“…In the FDA pooled analysis of outcomes of anti-PD-(L)1 therapy (IO) with or without chemotherapy (chemo) for first line treatment of patients with NSCLC and PD-L1 score ≥50% ( 80 ), never-smokers appeared to have better results with the association of IO-chemo in all the outcomes evaluated: median OS NE vs 14.4 months (HR 0.39, 0.15-0.98), median PFS 10.2 vs 3.7 months (HR 0.46, 0.23-0.92) and ORR 69% vs 28% (OR 4.6, 1.5-14.5).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In der ersten Analyse wurden von der FDA zugelassene Regime für Tumoren ohne genetische Alterationen darauf untersucht, ob bei einer PD-L1-Expression ≥ 50 % die Notwendigkeit der Kombination einer immunonkologischen Substanz mit einer Chemotherapie notwendig ist 1 . In die Auswertung flossen die Daten von 9084 therapienaiven NSCLC-Patienten aus 12 randomisierten Studien ein, von denen 3189 Patienten einen PD-L1-Score ≥ 50 % aufwiesen.…”
Section: Stellenwert Der Chemotherapie Im Kontext Diskutierenunclassified
“…Durch die ständig fortschreitende Entwicklung neuer Wirksubstanzen und die Untersuchung neuer Kombinationen in unterschiedlichen Therapielinien bedarf es einer ständigen Überarbeitung des Therapiealgorithmus. Die amerikanische Behörde FDA (U. S. Food and Drug Administration) präsentierte auf dem ASCO 2022 in 2 Vorträgen die Analyse der eingereichten Daten zur Optimierung der Erstlinientherapie beim fortgeschrittenen nicht-kleinzelligen Lungenkarzinom (NSCLC) 1 , 2…”
unclassified